2022
DOI: 10.1093/police/paac009
|View full text |Cite
|
Sign up to set email alerts
|

Educating Future Police Professionals Amid Covid-19 a UAE Perspective

Abstract: In 2020, as the world focused efforts to address the humanitarian challenges presented by the Covid-19 pandemic, the global education community was similarly challenged to demonstrate resilience and innovation to support a level of ‘normality’ for students at all levels and professions. The research presented in this article offers insight into the preparation and deployment of transitioning education of police students from face-to-face delivery to online delivery in an environment historically unfamiliar wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…By synthesizing the application of the metaverse in the creation of scenarios that can enhance comprehensive skill development, the study will provide information on how to improve police training and education. Besides, Davies and Al Sharefeen (2022) note that the emergence of the COVID -19 Pandemic necessitated the development of technology-based platforms of education and training for police officers to ensure that they can cope with the changing operational landscape. This study offers an in-depth analysis of how the metaverse can be used to mitigate COVID -19 -related challenges to education.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…By synthesizing the application of the metaverse in the creation of scenarios that can enhance comprehensive skill development, the study will provide information on how to improve police training and education. Besides, Davies and Al Sharefeen (2022) note that the emergence of the COVID -19 Pandemic necessitated the development of technology-based platforms of education and training for police officers to ensure that they can cope with the changing operational landscape. This study offers an in-depth analysis of how the metaverse can be used to mitigate COVID -19 -related challenges to education.…”
Section: Importance Of the Studymentioning
confidence: 99%
“…Studies in comparable milieus were conducted and reported on successes and challenges associated with student and faculty adoption of online learning (see Adnan and Anwar, 2020 ; Davies and Al Sharefeen, 2022 , 2022a ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the impact on training, recent research suggests that police educational institutions have experienced a number of impacts related to the COVID-19 pandemic. This means that different police educational institutions have responded differently not only to the challenges of the pandemic, but also to their willingness to embrace more online and alternative strategies for curriculum delivery (Davies & Al Sharefeen, 2022;White, Schafer, & Kyle, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%